Dynamic Method for Liaison of Community Pharmacists with National Programme for Tuberculosis Control: Efforts to Harness Untapped Opportunities - Ramasamy, Rajeswari; Mohanta, Guru Prasad; Hiremath, Shobha Rani R; Ramnarayanan, Chandramouli; Dang, Raman; Gharat, Manjiri S (Indian Journal of Pharmaceutical Education and Research, 2020)
Context: Revised National Tuberculosis Control Program (RNTCP) - Directly Observed Treatment-Short course (DOTS) strategy to involve Community Pharmacist (CPs), was conceived and implemented in India, with the objective of improving accessibility of Tuberculosis free medicines. Though the RNTCP personnel in the study area had tried to create liaison with CPs; and to train them in DOTS provision roles, it was not successful as CPs were not forthcoming to be a part RNTCP - DOTS paradigm. Hence this study was ideated and executed to develop a liaison model between CP and RNTCP personnel, to support the delivery of DOTS treatment under RNTCP programme. This article discusses the liaison method followed by the researchers to integrate the CPs with RNTCP’S TB centres in Bangalore City. Aim: To establish liaison between community pharmacists and RNTCP personnel to strengthen Public Private Mix (PPM) Partnership for providing TB care role in Bengaluru City, India. Methodology: An educational interventional study involving CPs in Bengaluru City was conducted with the regulatory support from Drugs Control department, Karnataka.Awareness and Training was given on the basis of the RNTCP training module for Community Pharmacist. The change in the level of awareness on existence of PPM RNTCP strategy among community pharmacist; and the percentage of pharmacists showing interest for TB care role after the program was measured. Results and Discussion: Out of 125 CPs representations, 93 CPs enrolled them as Private DOTS providers immediately after programme. The change in the Level of Awareness on the existence of TB-DOTS provider role was found to be 100% in this study. This result clearly points to the fact that CPs needs to be sensitized. Conclusion: The policy level changes in the ease of enrolling CPs to be a DOTS provider under the aegis of drugs control department, needs to be revisited and rethought in RNTCP’s national strategy for pharmacists.
Keywords: Tuberculosis; DOTS; Community Pharmacist; Public Private Mix Partnership; RNTCP; Public Health; DOTS Provider; National Programme